Poor Relief as a Legal Issue in the Austrian Monarchy - Zdeňka Stoklásková (Journal on European History of Law, 2023)
This study examines the origin of legal tools for the creation of systematic poor relief in the Austrian monarchy from the period of Joseph II. It is possible to find a certain kind of legal protection for Austrian state citizens in Joseph’s Civil Code from 1786 and in the General Civil Code from 1811. The paper analyses the legal principles leading to the establishment of the home community principle for Austrian state citizens, which was essential for providing aid to the poor. Attention focuses on an interpretation of problematic legal terms such as „home settling“ or „häusliche Niederlassung“, the implementation of which was resolved in legal disputes between state authorities. The author discusses the decrees of the Supreme Court of Justice in Vienna from the last quarter of the 19th century which concerned disputes between municipalities relating to the reimbursement of the costs of poor relief.